Christ as once for all sacrifice: a cultrual reading of Hebrews - K. J. Pali (Acta Theologica)
The practice of sacrifices to the ancestors is still prevalent among some African Christians and it is inspired by various factors such as religious considerations or political aspirations through African renaissance. Furthermore, scholars argue as to whether this practice of sacrifices to the ancestors is Biblical or not. This article aims to determine that, from Hebrews, the demise of Old Testament sacrifices brings an end to ancestral sacrifice.